Acid‐sensing ion channels in trigeminal ganglion neurons innervating the orofacial region contribute to orofacial inflammatory pain. (February 2016) - Fu, Hui; Fang, Peng; Zhou, Hai‐Yun; Zhou, Jun; Yu, Xiao‐Wei; Ni, Ming; Zheng, Jie‐Yan; Jin, You; Chen, Jian‐Guo; Wang, Fang; Hu, Zhuang‐Li
Summary: Orofacial pain is a common clinical symptom that is accompanied by tooth pain, migraine and gingivitis. Accumulating evidence suggests that acid‐sensing ion channels (ASICs), especially ASIC3, can profoundly affect the physiological properties of nociception in peripheral sensory neurons. The aim of this study is to examine the contribution of ASICs in trigeminal ganglion (TG) neurons to orofacial inflammatory pain. A Western blot (WB), immunofluorescence assay of labelled trigeminal ganglion neurons, orofacial formalin test, cell preparation and electrophysiological experiments are performed. This study demonstrated that ASIC1, ASIC2a and ASIC3 are highly expressed in TG neurons innervating the orofacial region of rats. The amplitude of ASIC currents in these neurons increased 119.72% (for ASIC1‐like current) and 230.59% (for ASIC3‐like current) in the formalin‐induced orofacial inflammatory pain model. In addition, WB and immunofluorescence assay demonstrated a significantly augmented expression of ASICs in orofacial TG neurons during orofacial inflammation compared with the control group. The relative protein density of ASIC1, ASIC2a and ASIC3 also increased 58.82 ± 8.92%, 45.30 ± 11.42% and 55.32 ± 14.71%, respectively, compared with the control group. Furthermore, pharmacological blockade of ASICs and genetic deletion of ASIC1 attenuated the inflammation response. These findings indicate that peripheral inflammation can induce the upregulation of ASICs in TG neurons, causing orofacial inflammatory pain. Additionally, the specific inhibitor of ASICs may have a significant analgesic effect on orofacial inflammatory pain.